(untitled) (Research, Society and Development, 2022)
The changes brought about by technological advances led to the need to develop new ways of transmitting information and teaching, with great emphasis on Distance Education. Added to this are innovative teaching methodologies that seek to break the traditional pattern of education that has fixed roles of teacher and student, such as Project-Based Learning (PBL), resource that proposes a new way of teaching through the solution of practical questions by students. Thus, this article aimed to answer the following guiding question: “How has Problem-Based Learning been applied in the context of distance education and what are the benefits and challenges of its use?”. For this, an integrative review of academic literature related to experiences with PBL in different areas and levels of education was carried out. In the end, it was possible to identify that the use of this methodological tool for teaching on Distance Education generated benefits and manifests in the context of its applicability, such as: better time management; student performance; more dynamic classes; increased student participation and attention; more critical analysis in solving and presenting hypotheses for the proposed activities; better understanding of the content; greater flexibility in the collaborative teaching axis. On the other hand, difficulties were also recognized, such as: resource limitations; lack of technical domain, skills and handling of technological tools by the participants and resistance to the use of the methodology.